Possibilities of retrograde intrarenal surgery in the treatment of renal lower pole stones in children - Ilić, Predrag; Kostić, Dejan; Džambasanović, Slobodan; Janković, Mirjana; Kojović, Vladimir (Vojnosanitetski pregled, 2020)
Background/Aim. Renal stones located in the lower pole of kidney represent a serious challenge for surgical treatment in children. The options are: open surgery, extracorporeal shock-wave lithotripsy, percutaneous nephrolithotomy and retrograde intrarenal surgery. Reports about the endoscopic treatment in children are limited. The aim of the study was to evaluate the effectiveness of retrograde intrarenal surgery in pediatric patients with renal stones in lower pole of the kidney. Methods. We retrospectively analyzed the results of the retrograde intrarenal surgery in 24 patients with renal stones in lower pole, between April 2012 and April 2016. Flexible ureterorenoscopy in combination with holmium laser lithotripsy were performed. We considered stone fragment size 3 mm or less as a measure of sufficient fragmentation of the stone. Results. Mean duration of general anesthesia was 68 (range, 40–90) minutes. Duration of hospitalization was 1–3 (mean, 1.6) days. Complications were found after two (8.4%) surgical procedures: perirenal haematoma in one (4.2%) and urinoma in one (4.2%) patient. The stone was completely fragmented in 18 (75%) patients. In 3 (12.5%) patients the stone was incompletely fragmented and in 3 (12.5%) patients the stone was not fragmented. Double J stent was placed in 5 (21%) patients. Mean follow-up was 9 (range, 6–18) months. Conclusion. Retrograde intrarenal surgery in children is the least invasive, effective and safe surgical procedure for stones in lower pole of the kidney, with minimal complication rate. Unsuccessful treatment in some patients was due to loss of ureterorenoscope deflection with laser probe in working channel.